Analysis of the Fiscal Independence of the Regional Government of Timor Tengah Selatan Regency in Carrying Out Regional Government Affairs - Marianus E. Manggau; Nikson Tameno; Cicilia A. Tungga (Formosa Journal of Sustainable Research, 2023)
This study aims to analyze the level of fiscal independence and the government's performance in carrying out local government affairs in Timor Tengah Selatan Regency. This study uses a quantitative descriptive approach by calculating the level of fiscal independence and local government performance achievements. The results of this study indicate that the average fiscal independence of Timor Tengah Selatan Regency in 2016-2021 is based on an independence ratio of 7.23% so that it is classified according to the fiscal independence assessment criteria. High dependency on assistance from the central government through balancing/transfer funds, and if it is related to the pattern of relations between the central government and local governments, it is included in the category of instructive relationship patterns. While the average performance score of the TTS district government during the 2016-2021 period was 2.52 and was in the low category, in 2016 the TTS district government obtained a score of 2.63 with a moderate predicate, which is the highest achievement during the 2016- 2021